2022
DOI: 10.1155/2022/6493458
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Iron Oxide Nanoparticles against Breast Cancer

Abstract: Breast cancer is the most common cancer diagnosed in women, with an estimated 12% of women in the United States affected during their lifetime. Researchers have demonstrated that early detection, diagnosis, and treatment are pivotal to increasing survival. The advent of nanotechnology has yielded several novel advances and available modern methods within the clinic to detect and treat breast cancer. Inorganic nanoparticles are broadly utilized for cancer diagnosis and therapeutic purposes. Interestingly, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…Vaccination is the most successful way to prevent and control disease, and it has saved countless lives in both infectious disease and cancer treatment [5,22,23]. At present, nucleic acid vaccines are divided into two categories: plasmid DNA vaccines and mRNA vaccines, both of which have demonstrated potential [22].…”
Section: Mrna Vaccination and Mechanism Of Action Of Mrnamentioning
confidence: 99%
“…Vaccination is the most successful way to prevent and control disease, and it has saved countless lives in both infectious disease and cancer treatment [5,22,23]. At present, nucleic acid vaccines are divided into two categories: plasmid DNA vaccines and mRNA vaccines, both of which have demonstrated potential [22].…”
Section: Mrna Vaccination and Mechanism Of Action Of Mrnamentioning
confidence: 99%
“…Such metal anticancer complexes have broad prospects in the field of anticancer research. Hessam Hosseinkazemi et al [ 182 ] reported on the potential use of iron oxide nanoparticles as therapeutic drugs and acknowledged their superiority over traditional therapeutic drugs. Although only used for the treatment of iron-deficiency anemia and cancer, multiple experiments are currently being conducted to promote its clinical application.…”
Section: Metal Anticancer Drugsmentioning
confidence: 99%
“…Nanoscale devices and materials can deliver therapeutic drugs specifically to cancer cells, thereby reducing exposure to healthy tissues. [6,7] Nanoparticles (NPs) show particular promise in the treatment of lung cancer, where they can be utilized as drug delivery systems. Incorporating therapeutics that specifically target cancer cells into NPs has shown to be more effective for treatment with fewer side effects.…”
Section: Doi: 101002/adtp202300275mentioning
confidence: 99%